PSVIII-5 Genetic parameters of thrombin as a proxy for horn fly abundance in beef cattle. (8th October 2021) - Ling, Ashley S; Krause, Taylor; Warner, Amanda; Duggin, Jason; Heins, Bradley; Hinkle, Nancy; Aggrey, Samuel E; Pringle, Dean; Rekaya, Romdhane
Abstract: Horn flies (Haematobia irritans) are a major nuisance to cattle, especially in warm, humid regions, and are estimated to cause economic losses in excess of $1 billion annually to the U.S. beef cattle industry. Variation in horn fly tolerance has been reported within and across breeds, and heritability estimates ranging between 10 and 80% show a clear genetic basis. However, collecting fly abundance phenotypes is costly and logistically demanding, which precludes large-scale implementation. Consequently, finding correlated phenotypes and endo-phenotypes that are heritable and relatively easy to measure would facilitate implementation of horn fly tolerance genetic improvement programs. Thrombin (TH), a blood coagulation precursor, has a reported association with horn fly count variation within and across cattle breeds. In this study, the genetic basis of thrombin in beef cattle was investigated. Blood samples and horn fly count were collected on 360 cows and heifers twice during the summer of 2019 (June and August). Due to uncertainty associated with assessment of horn fly abundance and thrombin and the fact that economic losses occur only when fly abundance exceeds a certain threshold, thrombin was categorized into 4 classes (1=TH > 500 ng/ml; 2=250< TH< 500 ng/ml; 3=100< TH< 250 ng/ml; and 4=TH< 100 ng/ml). The trait was analyzed using linear (continuous) and threshold (discrete) mixed models. Both models included farm, pregnancy status, and cow age as fixed effects and additive and permanent environment random effects. The pedigree included 642 animals. Estimates of heritability were 0.24 and 0.29 using linear and threshold models, respectively. Estimates of repeatability were slightly higher using the threshold model (0.21 vs 0.19). Despite the small data size, all estimates were non-zero based on their respective highest posterior density intervals. These results indicate reasonable genetic variation for thrombin that could be harnessed for improvement of horn fly tolerance in cattle.